2010
DOI: 10.1007/s13277-010-0118-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of HE4 expression in pulmonary adenocarcinoma

Abstract: We investigated the possibility of human epididymis 4(HE4) to predict survival for patients with pulmonary adenocarcinoma. One hundred and thirty-seven patients with pulmonary adenocarcinoma underwent surgery in our institute from 2000 to 2008. We used immunohistochemical analysis to determine the expression of HE4 and compared with the clinicopathological factors and survival. Serum levels of HE4 in lung adenocarcinoma were investigated by enzyme immunometric assay. Fifty-seven of 137 cases (41.6%) were HE4 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 17 publications
8
37
2
Order By: Relevance
“…One of these studies examined a patient's serum prior to chemotherapy and failed to detect any association between HE4 level and histologic subtype among 153 metastatic lung cancer patients (20). Consistent with these studies, we have not observed such a higher cytoplasmic staining among our SCLC cases but HE4 expression among NSCLC cases is consistent with the literature (9,12). We observed HE4 expression in the cytoplasm of bronchial glands next to tumor cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…One of these studies examined a patient's serum prior to chemotherapy and failed to detect any association between HE4 level and histologic subtype among 153 metastatic lung cancer patients (20). Consistent with these studies, we have not observed such a higher cytoplasmic staining among our SCLC cases but HE4 expression among NSCLC cases is consistent with the literature (9,12). We observed HE4 expression in the cytoplasm of bronchial glands next to tumor cells.…”
Section: Discussionsupporting
confidence: 89%
“…Among locally advanced non-small cell lung cancer (NSCLC) patients, a higher serum level of HE4 has been found to predict non-responders to chemoradiotherapy (11). Moreover, HE4 expression had a 2-fold decrease in the 5-year disease-free survival compared to that in the negative expression group (12).…”
Section: Introductionmentioning
confidence: 99%
“…HE4 expression has been demonstrated in several lung cancer cell lines [9,79]. The highest HE4 tissue expression was detected in adenocarcinomas of the lung compared with small-cell, squamous, and large-cell lung cancers [81,82]. Nagy et al reported that serum HE4 was highly increased in male patients with lung cancers, even prior to asymptotic cases, indicating serum HE4 could be a sensitive marker for early diagnosis of lung cancer [83].…”
Section: Inflammatory Diseasementioning
confidence: 99%
“…15 Consequently, Iwahori et al and Liu et al investigated the diagnostic role of serum HE4 levels in NSCLC patients and in both studies, they differentiate lung cancer patients from healthy controls with high sensitivity (89.8%) and specificity (100%). 16,18 Recently, Cheng et al published a meta-analysis presenting the diagnostic accuracy of HE4 in lung cancer and indicated that the sensitivity and specificity of HE4 were 0.72 and 0.85, respectively, which are higher than the conventional biomarkers such as CEA, CYFRA21-1 and NSE.…”
Section: -mentioning
confidence: 99%
“…2,6,15,16,21 Lan et al examined the role of HE4 in the diagnosis and prognosis of patients with locally advanced NSCLC who received concurrent chemoradiotherapy (CRT). Their data showed that higher serum HE4 levels are associated with poor response to CRT, shorter relapse-free and overall survival.…”
Section: -mentioning
confidence: 99%